Analysis of Students' Dependence on AI in Completing Academic Assignments - Adinda Lestari; Chyntya Sri Ulina Br Kaban; Ikhwan El Akmal Pakpahan (Jurnal Multidisiplin Sahombu, 2026)
The development of artificial intelligence (AI) has driven significant changes in students' academic activities, particularly in completing coursework. The ease, speed, and ability of AI to assist with understanding material and formulating answers have led to its increasing use, but it also raises the potential for dependency. This study aims to analyze the level of student dependency on the use of AI in completing academic assignments and the relationship between this dependency and their completion. This study used a quantitative approach with a descriptive-correlational method. Data were collected through a Likert-scale questionnaire distributed to 146 university students and analyzed using descriptive statistics, normality tests, linearity tests, and Pearson correlation tests using SPSS software. The results indicate that the level of dependency on AI is moderate, with the majority of students utilizing AI to improve the efficiency and ease of completing academic assignments. The correlation analysis revealed a positive and significant relationship between dependency on AI and completion of academic assignments. However, these findings also indicate the need for proportional use of AI so that the academic benefits obtained do not reduce students' independence and cognitive engagement in the learning process.